In-vitro evaluation of exotic Hevea genotypes for resistance to corynespora cassiicola - Achuo Enow A; Ebai Maxwell M; Mokoko Gobina S (Journal of Rubber Research, 2001)
Hevea leaf fall disease caused by Corynespora cassiicola (Berk & Curt) Wei, is one of the major disease constraints to the production of natural rubber (Hevea brasiliensis) in South Cameroon. Attempts to control this disease by traditionally recommended practices such as artificial defoliation or aerial spray of fungicides have not yielded satisfactory results in Cameroon. Production of disease resistant planting material may provide a more efficient disease control strategy. As part of a screening process of a large pool of Hevea genetic resources for disease resistance, we evaluated in-vitro, 28 genotypes collected from Amazonia. These genotypes were tested for resistance to two isolates of C. cassiicola (NKO1 and NKO2), obtained from different clones showing different levels of susceptibility to the disease in the same field in South Cameroon. The two isolates had similar growth characteristics on culture media. However, isolate NKO1 grew faster than NKO2 on Ptato Dextrose Agar and was also more virulent on the test material. The two isolates may belong to different races. To verify this, further characterisation of the isolates is recommended. Significant differences were observed in the response of the tested Hevea genotypes to each of the isolates. Genotypes AC/S/12/22, RO/07/48, and AC/B/19/22 had the highest resistance to both isolates. These could constitute good source material in breeding for disease resistance. Due to their high susceptibility to both isolates, genotypes AC/S/12/02, MT/1/25, MT/C/04/22, MT/C/04/27 and RO/C/08/33 may have to be avoided in any such breeding programme.
Keywords: Breeding; Cameroon; Corynespora cassiicola; Disease resistance; Genotypes; Hevea brasiliensis; In vitro; Leaf fall